Effects of bentonite nanoparticles inhalation on lung tissue and blood antioxidant indices in a rat model. (January 2020) - Masoudi, Fatemehsadat; Naghizadeh, Ali; Zardast, Mahmoud; Gholami, Abdullah; Farrokhfall, Khadijeh; Foadoddini, Mohsen; Mehrpour, Omid
Bentonite is an inorganic clay material that is often easily dispersed as fine particles by air and water circulation, and most people are exposed to different concentrations of bentonite particles. Therefore, the inhaled effects of bentonite nanoparticles (BNPs) were studied in Wistar rats. Seventy-five rats were divided into five groups of 15: four exposure groups (0.1, 0.5, 2, and 10 mg/m 3 of BNPs) and one control group. The rats were exposed for 30, 60, and 90 days to BNPs for 5 days a week (6 h/day) in whole-body inhalation chambers. Blood samples were collected to measure the levels of antioxidant activity of the contents such as total antioxidant capacity (TAC) and malondialdehyde (MDA). X-ray diffraction and scanning electron microscopy were used to identify nanoparticles. The results showed no significant difference in the effect of nanoparticles on levels of TAC and MDA in the studied groups based on the concentrations of nanoparticles. However, the level of MDA increased significantly with extending exposure time; there was a significant increase in the level of MDA content 90 days postexposure compared to 30 days postexposure at concentrations of 0.5, 2, and 10 mg/m 3 . Histopathological examination showed that inhalation exposure of rats to BNPs led to different histopathologic responses in the lung tissue, such as inflammatory infiltration, granulomatous inflammation, acute neutrophilic reaction in the early stages, and lung fibrosis. At the lowest concentration, BNPs have low or no toxicity, and inhalation of these nanoparticles at low concentrations does not affect the levels of MDA and TAC content. However, increased concentration and exposure time caused correspondingly greater increases in MDA and more damage to lung tissue.